Noncanonical Translation Initiation Comes of Age - Babitzke, Paul (J Bacteriol, 2017)
The canonical translation initiation mechanism involves base pairing between the mRNA and 16S rRNA. However, a variety of identified mechanisms deviate from this conventional route. Beck and Janssen (J Bacteriol 199:e00091-17, 2017, https://doi.org/10.1128/JB.00091-17) have recently described another noncanonical mode of translation initiation. Here, we describe how this process differs from previously reported mechanisms, with the hope that it will foster increased awareness of the diversity of regulatory mechanisms that await discovery.